Antimicrobial activity of Streptomyces griseoviridis K10 against ESBL Escherichia coli, MRSA, and other pathogenic microorganisms. Issue 1 (February 2020) - Warsito, M F; Isnaeni,; Kusumawati, I
Abstract: The emergence of resistant pathogenic bacteria is serious threat to global public health. This problem can be address through discovering new antibiotics from nature. Streptomyces are known as the source of more than fifty percent commercially available antibiotics, but it is predicted that only less than 5% were identified. Streptomyces griseoviridis K10 were fermented in ISP-4 medium pH 7.2 for four days in 32 °C incubated shaker with 150 rpm agitation. The antimicrobial activity of Streptomyces griseoviridis K10 were analyzed using diffusion method. The antibiotic production curves were made to determine the optimal antibiotic production time. The result showed that these bacteria had activity against extended-spectrum beta-lactamases (ESBL) Escherichia coli, Methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa ATCC 27853, Escherichia coli ATCC 25922, S. aureus ATCC 25923, and Candida albicans, with inhibitory zone of 17.25 ± 0.43 mm; 13.95 ± 0.60 mm; 20.96 ± 0.41 mm; 20.64 ± 0.92 mm; 21.73 ± 0.53 mm; and 16.90 ± 1.27 mm, respectively. The antibiotic production was optimum in the second and third days.